TRANSLATION TOOL TECHNOLOGY TREND : WHAT ARE THE IMPACTS FOR THE STUDENTS? - Eka Uli Putri Br Bangun; Siti Maisaroh Mustafa (International Journal of Educational Management and Innovation, 2021)
The popularization of the computer and its technology have brought about some significant changes.   Technology itself has impacted almost every aspect of life today, and education is no exception.   Technology provides not only a window to the world but also easy access to thousands of learning resources. Regarding English learning, translation is a part of learning activities in which students sometimes assigned for translation work. Hence, a specific translation tool, namely Google translate, is preferred and utilized.   This research aims to examine the impacts of using the translation tool for students and how frequently they use it in their learning activities. It is quantitative research and the methods of the data collections comprised tests, additional interviews and questionnaires. The samples of this research were 40 students at LP3I. It was evident that the translation tool had positive impacts on the students. The data could derive from the results of Pre-test and Post-test of the students. They got a higher score before and after using the translation tool. Although translation tool had good impacts for students, some problematic points were using the translation tool. Students suggested to check and recheck the result of their translation in the target language. The translation tool also helped students do writing tasks, even though there was some positive and negative impact on students' translation tool utilization.